Produção de gases de efeito estufa e potencial de geração de créditos de carbono em processos de tratamento de esgoto sanitário - Lima, Aline Pereira (Universidade Federal de São Carlos, 2012)
The concept of carbon credits came from the awareness of need to reduce greenhouse gas (GHG) emissions in order to combat the worsening of global warming, discussed and formalized in the Kyoto Protocol. Emission of greenhouse gases as methane, nitrous oxide and carbon dioxide is due to several activities, among them the wastewater treatment, both domestic and industrial. This paper presents an estimation of CH4 and N2O production and energy consumption in wastewater treatment systems most used in Brazil, on which mitigation scenarios were applied to show its representation in terms of carbon credits and monetary value. This work was based on the methodologies and procedures of the Intergovernmental Panel on Climate Change - IPCC. The results show that the largest volumes of GHGs are associated with anaerobic treatments, whose emissions may exceed 200 tCO2e/year. Both suggested mitigation proposals (replacement of anaerobic systems by open aerobic processes or introduction of mechanisms for capturing and burning methane in closed reactors) show a similar emission reduction, mostly between 100 and 150 tCO2e/year for attended population of 1000 persons. However, it was found that the credit potential is in the biogas combustion because aeration demands high energy consumption. This ability to generate carbon credits, from Clean Development Mechanism (CDM), can help soften some of the implementation costs of wastewater treatment plants, as well as stimulate its modernization.
Keywords: Engenharia urbana; Efeito estufa; Créditos de carbono; Tratamento de esgoto; Gases de efeito estufa; Greenhouse gases; Carbon Credits; Wastewater treatment; ENGENHARIAS